THE IMPLEMENTATION OF INTEGRATED CROPPING CALENDAR ON LOWLAND RICE FARMING IN BENGKULU CITY - Yuliarso, Muhammad Zulkarnain; Windirah, Nola; Widono, Septri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
Bengkulu Province has rice productivity that is able to keep up with Lampung and West Sumatra (Top Five in production and on top three in land ownership throughout Sumatra), although rice farmland ownership is relatively low (less than 0.8 hectares) ). The climate change issue in the last two decades has impacted a significant decrease in rice production in Bengkulu Province. The government offers the Cropping Calendar (Katam) program, a technology that is able to provide a various information related to the croping such as the prediction of the beginning of the rainy season, the beginning of the cropping season, cropping patterns, potential cropping area and others to overcome these problems and the City of Bengkulu has begun to implement the program. The purpose of this study is to analyze the level of application of integrated Cropping calendar by lowland rice farmers in Bengkulu City and analyze the correlation between internal and external factors of farmers with the level of Cropping calendar application. The basic method of this research is explanatory with a combined approach (quantitative and qualitative). The results showed that the level of application of integrated cropping calendar innovations in rice farmers was low. Farming experience, knowledge about cropping calendar, communication behavior, and social strengthening are significantly related to the level of application of cropping calendar innovation in rice farmers.